Equality Before the Law? Evaluating Criminal Case Outcomes in Canada - Trebilcock, Michael (2016)
One of our most strongly held ideals is that individuals receive equal treatment under the law. Incidents of wrongful conviction or wide disparities in sentencing, however, challenge this premise. While legal scholars have recently examined this premise, our understanding remains largely normative or anecdotal. Scholars have begun to identify factors that influence legal outcomes, yet this question has remained largely unexplored in Canada. This article seeks to advance this inquiry. Using unique data from both the Ontario courts and Legal Aid Ontario during 2007–2013, we find that outcomes in routine criminal cases vary in ways not summarily explained by differences in defendant or city characteristics. Cities differ in their use and expenditure of defendant legal representation in ways strongly correlated with outcomes, controlling for other factors. While only a first step, our article counsels strongly in favour of a systematic examination of case adjudication in Canada, and offers future avenues for research